Strategi kesopanan berbahasa masyarakat Bugis Pinrang Provinsi Sulawesi Selatan - Achmad, Syarifuddin (citeus, 2012)
The aims of this research is to explore and to represent the form and the characteristics of linguistic politeness, linguistic strategy, the realization and the implication of siri’ cultural value in Buginese Pinrang society. This research applied etnomethodology viewed from pragmatics, semiotics, and face wants concept from Brown and Levinson (1987). The results of this research show the characteristics and the forms of linguistic politeness through some morphemes marked such as prefixes t and ta, suffix pronouns ta, ki, ni and some vocabularies such as honorific vocabularies such as puang, andi, daeng, and some lexemes iye, tabe, taddampengenga, some pragmatic politeness in some maxims, such as generousity, approbation, modesty, and sympathy, and four strategies of linguistic politeness, namely bald on record strategy, positive, negative, off record strategy, and the realization and the implication of siri’ as a basic value such as ethics and language politeness, self image, courage, solidarity, and cooperation.